PHARMACOLOGICAL STUDIES ON PLANTS BELONGING TO THE FAMILY LEGUMINOSAE - KUMAR, AARUSHI; XAVIER, F. R. JOBI (International Journal of Current Pharmaceutical Research, 2020)
Objective: The study is an attempt to quantitatively measure the presence of Anti-Parkinsons drug Levodopa in members of the family Leguminosae. Methods: Reverse phase HPLC, Phytochemical analysis carried out using Bioinformatic tools (ChemMine and Cytoscape). The dried seed samples of Mucuna pruriens (Linn.), Cassia fistula (Linn.), Lathyrus odoratus (Linn.), Glycine max (L. Merr.), and Mimosa pudica (L) were selected for the study of Levodopa, and compared with Tecoma stans from the family Bignoniaceae., and antimicrobial activity was conducted on selected bacteria. Results: Mucuna pruriens showed the presence of Levodopa in quantifiable higher quantity i.e., 705.5985 ????g/20 ml, whereas other plant samples contained very less quantity. The antimicrobial activity of the selected plants on E. coli and Bacillus showed positive results. Conclusion: The study proves the presence of Anti-Parkinsons drug Levodopa in Mucuna pruriens, whereas absent in the other plants. The selected plants prove the anti-bacterial activity on the selected bacteria.